Mutual winding angles of particles in Brownian stochastic flows with zero top Lyapunov exponent - Kuznetsov, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
The investigation of the geometric properties of particles moving in stochastic flows leads to the study of their mutualwinding angles. The same problem for independent Brownian motions was solved in [10]. We generalize these results tothe case of isotropic Brownian stochastic flows with top Lyapunov exponent equal to zero.